Blast-Exposed Veterans With Mild Traumatic Brain Injury Show Greater Frontal Cortical Thinning and Poorer Executive Functioning - Clark, Alexandra L.; Merritt, Victoria C.; Bigler, Erin D.; Bangen, Katherine J.; Werhane, Madeleine; Sorg, Scott F.; Bondi, Mark W.; Schiehser, Dawn M.; Delano-Wood, Lisa (Frontiers in Neurology, 2018)
Objective: Blast exposure (BE) and mild traumatic brain injury (mTBI) have been independently linked to pathological brain changes. However, the combined effects of BE and mTBI on brain structure have yet to be characterized. Therefore, we investigated whether regional differences in cortical thickness exist between mTBI Veterans with and without BE while on deployment. We also examined whether cortical thickness (CT) and cognitive performance differed among mTBI Veterans with low versus high levels of cumulative BE. Methods: 89 Veterans with mTBI underwent neuroimaging and completed neuropsychological testing and self-report symptom rating scales. Analyses of covariance (ANCOVA) were used to compare blast-exposed Veterans (mTBI+BE, n=60) to those without BE (mTBI-BE, n=29) on CT of frontal and temporal a priori regions of interest (ROIs). Next, multiple regression analyses were used to examine whether CT and performance on an executive function composite differed among mTBI Veterans with low (mTBI+BE Low, n = 27) versus high (mTBI+BE High, n = 33) levels of cumulative BE. Results: Adjusting for age, number of TBIs, and PTSD symptoms, the mTBI+BE group showed significant cortical thinning in frontal regions (i.e., left orbitofrontal cortex [p = .045], left middle frontal gyrus [p = .023], and right inferior frontal gyrus [p = .034]) compared to the mTBI-BE group. No significant group differences in CT were observed for temporal regions (p’s > .05). Multiple regression analyses revealed a significant cumulative BE x CT interaction for the left orbitofrontal cortex (p = .001) and left middle frontal gyrus (p = .020); reduced CT was associated with worse cognitive performance in the mTBI+BE High group but not the mTBI+BE Low group. Conclusions: Findings show that Veterans with mTBI and BE may be at risk for cortical thinning post-deployment. Moreover, our results demonstrate that reductions in CT are associated with worse executive functioning among Veterans with high levels of cumulative BE. Future longitudinal studies are needed to determine whether BE exacerbates mTBI-related cortical thinning or independently negatively influences gray matter structure. Word Count: 330